Implementasi Media Google Classroom pada Mata Pelajaran Pendidikan Agama Islam di Era Pandemi - Farida Isroani; Muflihaini (Medan Resource Center, 2022)
This study aims to (1) reveal PAI learning through Google Classroom media in the midst of the Covid-19 pandemic, (2) find out the supporting and inhibiting factors for PAI learning through Google Classroom media in the midst of the Covid-19 pandemic, (3) school solutions and efforts and stakeholders to achieve PAI learning goals through Google Classroom media in the midst of the Covid-19 pandemic. The researcher used descriptive qualitative method. Research data obtained through in-depth interviews, observation, and documentation. The informants in this study were theprincipal, the head of the curriculum, PAI educators, homeroom teachers, class X students and guardians of students. Researchers used data analysis techniques, including data reduction, data presentation, drawing conclusions and checking the validity of the data. The results showed that, (1) PAI learning management in the evaluation of psychomotor aspects has not been implemented, (2) learning supporting factors, namely the existence workshops oflearning Google Classroom, strong signals and internet quotas, students having smartphones, and guardians of students being able to monitor and control students. learn while at home. Meanwhile, the inhibiting factors for learning are bad signals due to natural conditions and the concentration of students is easily disturbed, (3) the application of combined PAI learning, namely 50% face-to-face and 100% online requires good synergy between students, educators, families and communities. in order to achieve PAI learning objectives in the midst of the Covid-19 pandemic.